The Relationship between Activity Based Costing, Business Strategy and Performance in Moroccan - Azzouz Elhamma; Zhang Yi Fei (Journal of Accounting and Management Information Systems (JAMIS), 2013)
The Activity Based Costing (ABC) represents a new model in the management accounting. In recent decades, it has been the subject of several research papers, especially in developed countries (USA, UK, France...). However, this type of works is still absent in the Arab countries. In this context, this article highlights the results of an empirical study on the relationship between ABC, business strategy and organizational performance in 62 Moroccan enterprises. 12.9% of the responding companies reported using the ABC method. The results using logistic regression indicate that the business strategy has not a significant influence on the use of this new method of the management accounting. Also, we found that the management accounting system based on ABC method results in a better performance for enterprises that have adopted it. Finally, we demonstrated that the both types of firms (prospectors and defenders) have an interest to adopt the ABC method.
Keywords: M41; M21; 650; Activity Based Costing (ABC) – Business strategy – Prospectors – Defenders – Organizational performance